ANALISIS KEJADIAN STROKE BERULANG PADA PASIEN YANG MENGGUNAKAN ANTIPLATELET DI RUMAH SAKIT X CIAMIS: ANALYSIS OF RECURRENT STROKE INCIDENTS IN PATIENTS USING ANTIPLATELETTS AT X CIAMIS HOSPITAL - Wisastry, Seisa; Ilham Alifiar; Citra Dewi Salasanti; Alifiar, Ilham; Salasanti, Citra Dewi (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Stroke is an acute and focal neurological deficit syndrome, which is clinically defined as the result of blood vessel injury in the central nervous system caused by rupture and blockage of blood vessels to the brain which results in reduced energy and the brain lacking nutrition. The aim of the study was to analyze the incidence of recurrent stroke in patients using antiplatelet drugs single aspirin, single clopidogrel and the combination at Hospital primary data obtained from the patient's medical record. Data and frequencies collected through patient medical records were analyzed using the chi-square test to determine the relationship between antiplatelet use and recurrent stroke. The results of this study showed that the number of stroke patients was 368 and recurrent stroke was 32 patients with an average duration of stroke recurrence, namely single aspirin 127.86 days, single clopidogrel 77 days, and the combination 237.39 days. From the data obtained, it can be concluded that Antiplatelet administration can affect the time to recurrent stroke. Keywords: Stroke, Antiplatelet, Aspirin, Clopidogrel, Combination